The synthesis of decades of groundwater knowledge: the new Hydrogeological Map of Rome - La Vigna, Francesco; Mazza, Roberto; Amanti, Marco; Di Salvo, Cristina; Petitta, Marco; Pizzino, Luca (Acque Sotterranee - Italian Journal of Groundwater, 2015)
This paper describes the contents and the path taken to get to the new Hydrogeological map of the City of Rome. The map, which is the result of a combination of "expert elaborations" and GIS processing performed using the most recent available data, extends to the entire municipality (1285 km2) and is based on both the most recent scientific studies on groundwater field and new survey activities carried out in order to fill the data gaps in several areas of the examined territory. The work represents also an example of inter-institutional collaboration between government agencies, research institutes and universities.